Vocational rehabilitation following traumatic brain injury: what is the evidence for clinical practice? - Phillips, Julie; Radford, Kathryn A. (Whitehouse publishing, 2014)
Traumatic brain injury (TBI) typically affects young adults with potentially many years of working life ahead of them. For people who were in work prior to their injury, return to work (RTW) is a common goal. However, a systematic review of RTW rates for people with TBI who were in work prior to their injury found that approximately 41% were in work at one and two years post TBI [1]. Since TBI is a leading cause of morbidity worldwide in young adults [2], this discrepancy between what people with TBI want and what they achieve is important. The question is does the research evidence inform clinicians how to help a person with TBI return to work?